Beschrijving van Maranhão: a Amazônia nos relatórios holandeses na época da Guerra de Flandres (1621-1644) - Alirio Cardoso (Topoi)
ABSTRACT In 1641, at the time of the greatest internationalization of the Spanish-Dutch War, the Netherlands invaded the captaincy of Maranhão, following an agenda established by the Heren XIX on the basis of a series of reports produced about the region. This documentation seeks to insert the Portuguese Amazon into a global scenario, but also clarifies much about the Netherlands’ expectations with respect to this immense territory. Based on such documents, this paper aims to discuss the role of Maranhão, Pará, and Cabo do Norte in the last phase of the Flanders War, between the decades of 1620 and 1640.